Position of Spain in the global tourism market: its competitive capacity and priorities - Andriy Melnyk; Nadiia Melnyk; Yaroslava Korobeinykova; Olena Pobigun; Iryna Ierko (Jan Długosz University in Częstochowa, 2023)
The article is devoted to the study of Spain's place in the world tourism market and determines the specialization of the country's recreational economy. The tourist potential of Spain is characterized. Equal attention is paid to the research devoted to natural recreational resources as well as historical and cultural heritage sites. The role of tourist infrastructure in the development of the country's tourism sector is outlined. Besides, the paper presents recreational zoning of the territory of Spain. The intensity, dynamics and geography of incoming and outgoing flows, features of domestic tourism, as well as revenues from international tourism and average tourist costs are analyzed. In addition to current data, the dynamics of the main statistical indicators of international tourism are traced. The impact of the global pandemic COVID-19 on the tourism industry of the studied country is estimated. The article depicts the main problems inherent in the Spanish tourism industry, in particular, economic, environmental and social problems. Simultaneously, the main priorities of Spain in the world tourism market are defined. The study was conducted on the basis of analysis of statistical reports and material data of UNWTO and the Institute of National Statistics of Spain, the Alliance for Excellence in Tourism, i.e. Exceltur. The methodological tools of the study involve analytical, statistical, comparative-geographical, mathematical methods, as well as methods of generalization and systematization, etc.